2019
DOI: 10.12928/jehcp.v8i2.12617
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Participation in Volunteering Based on Personality Characteristics

Abstract: The main goal of this research was to examine whether big five personality traits can predict participation in volunteering. A total of 420 participants consisting of 215 volunteers and 205 nonvolunteers from various regions in Indonesia completed an inventory of the big five personality traits. The preliminary analysis using independent sample t-test found that the openness, extraversion, agreeableness, conscientiousness, and emotional stability of volunteer samples were significantly higher than non-voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A relationship between volunteering and personality traits was reported in several studies [6,17,23,41,42]. Personality traits that influence volunteering are extraversion [6], empathy [41] and conscientiousness [42]. Extraversion is characterized as being friendly, sociable, active, talkative, and outgoing [6].…”
Section: Volunteerism and Personality Traitsmentioning
confidence: 94%
See 3 more Smart Citations
“…A relationship between volunteering and personality traits was reported in several studies [6,17,23,41,42]. Personality traits that influence volunteering are extraversion [6], empathy [41] and conscientiousness [42]. Extraversion is characterized as being friendly, sociable, active, talkative, and outgoing [6].…”
Section: Volunteerism and Personality Traitsmentioning
confidence: 94%
“…Conscientiousness is a personality trait that relates to being responsible, self-organized, efficient and hardworking. This also includes characteristics of order and logic [7,42]. People with a high level of conscientiousness tend to manage their time to carry out their social obligations such as participating in volunteer activities [42].…”
Section: Volunteerism and Personality Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, the personality traits of an altruistic attitude [ 26 ], low neuroticism, and high extraversion of volunteers related to better self-rated health [ 27 ] may neutralize the adverse impact of insomnia on subjective well-being. In contrast, other characteristics of volunteers, such as conscientiousness [ 28 ], may exaggerate the unfavorable influence of insomnia on subjective well-being because they may conflict with the core nature of good sleep, including automaticity (circadian and homeostatic regulation) and plasticity (accommodation to real-world circumstances) [ 29 ]. In the literature, only one study has demonstrated how ethnicity moderates the association between insomnia and positive mood [ 30 ], one domain of subjective well-being.…”
Section: Introductionmentioning
confidence: 99%